A Survey of Open Processor Core Licensing (Journal of Open Law, Technology & Society, 2019)
In the Spring of 2018, Western Digital Corporation commissioned Andrew Katz of Moorcrofts LLP to prepare a survey of open processor core licensing. This is an edited version of that report.